2020
DOI: 10.1128/aac.00136-20
|View full text |Cite
|
Sign up to set email alerts
|

Topical Antibiotic Elution in a Collagen-Rich Hydrogel Successfully Inhibits Bacterial Growth and Biofilm Formation In Vitro

Abstract: Background: Chronic wounds are a prominent concern, accounting for $25 billion of healthcare costs annually. Biofilms have been implicated in delayed wound closure, but treatment options continue to be limited and susceptible to developing antibiotic resistance. A novel collagen-rich hydrogel derived from human extracellular matrix presents an avenue for treating chronic wounds by providing appropriate extracellular proteins for healing and promoting neovascularization. Using the hydrogel as a delivery system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…Collagen wound dressings contain collagen blended with natural and synthetic polymers such as polyethylene oxide, poly (L-lactic acid), hyaluronic acid, elastin and silk fibroin, alginate, chitosan, etc [ 73 , 81 , 82 , 83 , 84 , 85 ]. These blended fabrications have incorporated other additives such as insulin [ 86 ], antibiotics [ 87 , 88 , 89 , 90 , 91 , 92 ] or gold nanoparticles [ 93 , 94 , 95 ] and have been tested mostly in in vitro studies or small animal models of wound healing. An evidence-based review of clinical studies on antibacterial integrated collagen wound dressings indicated that most studies were limited by small sample sizes and mixed chronic wound etiologies [ 46 ].…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen wound dressings contain collagen blended with natural and synthetic polymers such as polyethylene oxide, poly (L-lactic acid), hyaluronic acid, elastin and silk fibroin, alginate, chitosan, etc [ 73 , 81 , 82 , 83 , 84 , 85 ]. These blended fabrications have incorporated other additives such as insulin [ 86 ], antibiotics [ 87 , 88 , 89 , 90 , 91 , 92 ] or gold nanoparticles [ 93 , 94 , 95 ] and have been tested mostly in in vitro studies or small animal models of wound healing. An evidence-based review of clinical studies on antibacterial integrated collagen wound dressings indicated that most studies were limited by small sample sizes and mixed chronic wound etiologies [ 46 ].…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…Collagen is also used as a surface coating to enhance moisture retention and promote cell adhesion within scaffolds/matrices [ 73 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Water retention is important to keep the wound bed moist.…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…The H&E and Masson’s trichrome staining of the wound tissue on Day 10 and Day 20 were performed. As shown in Figure 5 f, less inflammatory cells in the QSPI-2.0 group and Alginate Ag group were observed compared with the Tegaderm TM film group on Day 10, which was probably due to QSPI-2.0 and Alginate Ag inhibiting bacterial infection-induced inflammation [ 25 ]. Granulation tissue formation is a critical stage during the wound healing process, where the injury is filled with a matrix of fibrous connective tissue and blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…27 Collagen-rich hydrogels were used as a delivery vehicle to offer controlled elution of gentamycin for bacterial growth inhibition (Pseudomonas aeruginosa) and disruption of biofilm formation. 47 Silica-collagen Type I nanocomposite hydrogels were loaded with antibiotics, gentamicin, and rifamycin. 48 The developed formulations were assessed for antimicrobial efficiency against P. aeruginosa and Staphylococcus aureus.…”
Section: Anti-inflammatory and Antibiotics Based Hydrogelsmentioning
confidence: 99%